Epigenetics of psoriatic disease: A systematic review and critical appraisal. (March 2017) - Pollock, Remy A.; Abji, Fatima; Gladman, Dafna D.
Abstract: Psoriasis is an inflammatory disease of the skin that is sometimes accompanied by an auto-inflammatory arthritis called psoriatic arthritis (PsA). Psoriasis and PsA are multifactorial diseases that result from complex interactions of environmental and genetic risk factors. Epigenetic marks, which are labile chemical marks with diverse functions, form a layer of biological information that sits at the interface of genetics and the environment. Aberrant epigenetic regulation has been previously implicated in other rheumatological disorders. The purpose of this review is to summarize and critically evaluate the nascent literature on epigenetics in psoriasis and PsA. A systematic review yielded 52 primary articles after applying inclusion and exclusion criteria. Data were extracted using a standardized template and study quality assessed using a methodological quality checklist. Studies reflect a broad range of epigenetic sub-disciplines, the most common being DNA methylation, followed by the parent of origin effect or genomic imprinting, expression or activity of epigenetic modifying enzymes, and histone modifications. Epidemiological studies demonstrating excessive paternal transmission provided the earliest evidence of epigenetic deregulation in psoriatic disease, however few studies have examined its molecular mechanisms. Methylation studies evolved rapidly from low resolution global to targeted analyses of known psoriatic disease susceptibility loci such as HLA-C*0602 . The recent explosion of epigenome-wide association studies has provided us with novel insights into psoriasis pathogenesis, and the mechanism of action of UVB, methotrexate, and anti-TNF therapies, as well as molecular signatures of psoriasis that may have clinical relevance. Finally, recent studies of pharmacological inhibitors of epigenetic modifier enzymes demonstrate their potential applicability as novel treatment modalities for psoriasis. Challenges of epigenetics research in psoriasis and PsA were identified and future perspectives are discussed herein. Highlights: Extensive epigenetic changes have been characterized in diverse tissues from psoriasis patients. Epigenome wide studies provide insight into psoriasis pathogenesis and drug mechanisms of action. Epigenome modifying enzymes are potential new targets for psoriasis treatment. Knowledge of the epigenetic differences between psoriasis and psoriatic arthritis patients may be clinically useful. 52 full-length papers and abstracts on epigenetics of psoriatic disease were published from 1946-present.